Penonton Anak dan Remaja Terkait Program Acara Indonesian Idol Junior 2016: Studi Resepsi Pada Kontestan Anak yang Menyanyikan Lagu-Lagu Orang Dewasa - Lestari, Anna Puji (Universitas Semarang, 2017)
This research examines about interpretation of teenagers and childrens spectatorship about contestants Indonesian Idol Junior 2016 who sang adult s song. This research used critical paradigm through cultural studies approach. Critical theory used in this research is commodification theory of Vincent Mosco to show that Indonesian Idol Junior exploit the contestants. The method is reception analysis which dismantle various interpretations of media content by small number viewers (Downing, 1990: 162). Based on research results, Elementary School Children are vulnerable to the media negative impact. Representation of television shows about children singing adult songs for an informant (Elementary School) is interpreted by dominan reading, and the three other respondents interpreted as negotiation readers (Junior and Senior High School). It means that Junior and Senior High School Students have adequate knowledge structure. The result also stated that all informants do not have knowledge about commodification broadcasting industry.